Evaluasi Pembelajaran Tematik dengan Sistem Daring Pada Siswa Kelas 4 SD - Imam Fatkhul Malik; Sofiatun Sopiatun; Taufiqur Rohman (Peneliti.net, 2021)
This research aims to ; 1) knowing the factors that support and hinder in thematic learning with an online system. 2) aims to determine the evaluation of the thematic learning program with an online system for grade 4 students at SD Negeri Banyubiru 04 Year 2020/2021. This study uses a qualitative approach. The respondents of this study were the principal and homeroom teacher. Collecting data using interview, observation, and documentation methods. Data analysis in the study was carried out by means of data reduction, data presentation, and drawing conclusions. Checking the validity of the data using data triangulation. The results of this study conclude; 1) implementation of thematic learning in grade 4 SD Negeri Banyubiru 04; 2) thematic learning barriers in grade 4 students of SD Negeri Banyubiru 04; 3) programs that need to be improved, eliminated, and continued; 4) planning thematic learning for 4th graders at SD Negeri Banyubiru 04.